Level of compliance in contact lens wearing medical doctors in Nepal - Sapkota, Kishor (2015)
PURPOSES: To determine the level of compliance and major non-compliant behaviors in contact lens (CL) wearing medical doctors (MDs) and to compare it with age matched CL wearing normal subjects with no medical background (NS). METHODS: Thirty-nine current CL wearing MDs, who were prescribed CLs in Nepal Eye Hospital, Kathmandu, Nepal, between 2007 and 2011, were interviewed on ten modifiable compliant behaviors regarding lens care and maintenance. The level of compliance and the rate of non-compliance for each behavior were determined and compared with NS. RESULTS: Level of compliance was good, average and poor in 35.9%, 48.7% and 15.4% of MDs, respectively. There was no significant difference in compliance between MDs and NS (p=0.209). Level of compliance was not associated with age, gender and duration of lens wear (p>0.05). Compliance rate varied according to different behaviors, achieving a good compliance level of 95% for hand hygiene, avoidance of water contact and not sleeping with lenses. There was poor compliance for topping up solution (53.8%) and lens case replacement (15.4%). CONCLUSION: About one third of MDs had a good level of compliance. Level of compliance and compliance rate of different behaviors were similar in MDs and NS. Periodic lens case replacement was the most neglected behavior in CL wearers for this region.